The genome sequence of the Scarlet Tiger moth, Callimorpha dominula (Linnaeus, 1758) - Boyes, D; Holland, PWH (F1000 Research Ltd, 2024)
We present a genome assembly from an individual male Callimorpha dominula (the Scarlet Tiger moth; Arthropoda; Insecta; Lepidoptera; Erebidae). The genome sequence is 658.1 megabases in span. Most of the assembly is scaffolded into 31 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 15.45 kilobases in length. Gene annotation of this assembly on Ensembl identified 20,234 protein coding genes.